2007
DOI: 10.1080/10635150701258787
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Genealogical Nonmonophyly in Species of Pinus Subgenus Strobus

Abstract: Phylogenetic relationships among Pinus species from subgenus Strobus remain unresolved despite combined efforts based on nrITS and cpDNA. To provide greater resolution among these taxa, a 900-bp intron from a late embryogenesis abundant (LEA)-like gene (IFG8612)was sequenced from 39 pine species, with two or more alleles representing 33 species. Nineteen of 33 species exhibited allelic nonmonphyly in the strict consensus tree, and 10 deviated significantly from allelic monophyly based on topology incongruence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
117
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(125 citation statements)
references
References 95 publications
(123 reference statements)
7
117
0
1
Order By: Relevance
“…However, recent phylogenetic, DNA-based studies (Liston et al 1999Gernandt et al 2005;Eckert and Hall 2006;Syring et al 2005Syring et al , 2007 show no evidence for monophyly in subsections Cembrae and Strobi and thus, merge the two into a new subsection Strobus. Whitebark Pine forms a clade with the 12 Eurasian species in Strobus plus Sugar Pine (P. lambertiana), another North American species.…”
Section: List Ofmentioning
confidence: 98%
“…However, recent phylogenetic, DNA-based studies (Liston et al 1999Gernandt et al 2005;Eckert and Hall 2006;Syring et al 2005Syring et al , 2007 show no evidence for monophyly in subsections Cembrae and Strobi and thus, merge the two into a new subsection Strobus. Whitebark Pine forms a clade with the 12 Eurasian species in Strobus plus Sugar Pine (P. lambertiana), another North American species.…”
Section: List Ofmentioning
confidence: 98%
“…This effect, moreover, is likely related to standing levels of population structure, our conservative sequence analysis pipeline, and inclusion of small coverage classes (i.e., n = 2-5). We have also used a recently diverged outgroup, and only a single sequence from this outgroup for analysis, that may in fact not be reciprocally monophyletic (Syring et al 2007). As such, estimates of divergence may be biased and thus by extension so would estimates of long-term positive selection.…”
Section: Limitations and Conclusionmentioning
confidence: 99%
“…On the basis of pioneer works of Shaw (1914), Mirov (1967) and, Little and Critchfield (1969) their taxonomic treatments are used widely and, subgenera Pinus and Strobus are accepted. Several revisions have made adjustments to the species status and modified the taxonomic treatment at the ranks of subgenera, sections and/or subsections (Farjon 1984;Farjon and Styles 1997;Gernandt et al 2003Gernandt et al , 2005Price et al 1998;Liston et al 1999;Syring et al 2007;Hernández-León et al 2013). In recent years molecular phylogenetic analyses using various DNA sequences of cytoplasmic and nuclear genomes were applied frequently to phylogenetic and taxonomic studies on Pinus species, and revealed reliable phylogenetic relationships among species.…”
Section: Abstract: Chromosome Fluorescent Banding Haploxylone Pinementioning
confidence: 99%